Students’ Originality in Expressing Their Ideas, Thoughts and Opinion in the Writing - Setiawati, A S; Oesman, A M; Wardhana, C K; Ramdhani, F; Ozy, J D A (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research aims to see how original students express their ideas, thoughts and opinions through essays. The research approach used is quantitative and qualitative. The data were obtained from the scores of students’ essays which were determined using an assessment rubric for the instrument. The essay consisted of 4 themes written by 63 students with a total of 252 essays. The results of quantitative analysis show that the level of originality of students’ thinking, opinions, and ideas has increased from one theme to another. The low level of originality can be seen in essays on the theme of “Supootsu to Shiai” (Sports and Matches). Students only repeat the opinions expressed by experts contained in newspaper articles or other references they read. Then, qualitatively average students have the ability to express opinions in sentences which are general ideas but expressed using their own language style. Based on the results of this study, it can be concluded that the Japanese language education study program students of UNNES have good abilities in expressing original ideas and opinions. This research has had an impact on increasing the ability to think creatively in terms of originality.